IDENTIFIKASI JENIS TUMBUHAN BAWAH YANG BERKHASIAT OBAT DI KAWASAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA - Yohanes Ason; Farah Diba; M Sofwan Anwari (Universitas Tanjungpura, 2018)
Understorey plants has many function, beside for the ornamental plants, it also has a function for medicinal plants. The research aimed to exploration understorey plant in Arboretum Sylva Universitas Tanjungpura and identification the understorey plants as medicinal plant. Arboretum Sylva Universitas Tanjungpura was located in the central of Pontianak City with average area around 3.2 hectares. The methods for exploration and identification the understorey plants were with inventory methods in all area of arboretum. The plant was collected and identification the used of plant to medicine was conduct by in depth interview with the person who has used the plants and from references of literature. The result of research found 23 understorey plants and divided into 19 families. The understorey plants which has a function for medicinal plants consist of Imperata cylindrica, Asplenium nidus, Lophatherum gracile, Stenochlaena palustris, Piper aduncum Lim, Melastoma malabathricum, Mimosa pudica, Ageratum conyzoides, Pyrrosia piloselloides, Justicia gendarussa, Cordyline fruiticosa, Sansevieria trifasciata, Manihot esculenta, Capsicum frutescens, Nymphaea alba, Ananas comosus, Euphorbia tithymaloides, Phyllanthus urinaria, Saccharum officinarum, Alpinia galanga, Aloe vera, Piper ningrum and Pandanus amaryllifolius. The families of understorey plants consist of Poaceace, Aspleniaceae, Blechnaceae, Piperaceace, Melastomaceae, Fabaceae, Asteraceae, Polypodiaceae, Acanthaceae, Asparagaceae, Ruscaceae, Euphorbiaceae, Solanaceae, Nymphaeaceae, Bromeliaceae, Phyllanthaceae, Zingiberaceae, Xanthorrhoeaceae, and Pandanaceae. The plants use to overcome the fever, headache, reduce high blood pressure, and anti-inflamation.Keyword: Arboretum Sylva, fever, medicinal plants, understorey plants, Zingiberaceae